2019
DOI: 10.3390/ijms20194673
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotics and Their Potential Applications in Early Life Nutrition and Beyond

Abstract: Postbiotics are functional bioactive compounds, generated in a matrix during fermentation, which may be used to promote health. The term postbiotics can be regarded as an umbrella term for all synonyms and related terms of these microbial fermentation components. Therefore, postbiotics can include many different constituents including metabolites, short-chain fatty acids (SCFAs), microbial cell fractions, functional proteins, extracellular polysaccharides (EPS), cell lysates, teichoic acid, peptidoglycan-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
273
0
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(296 citation statements)
references
References 114 publications
2
273
0
21
Order By: Relevance
“…Nevertheless, the review found that a few cases in non-healthy infants (e.g., short bowel syndrome) fed with acidified formulas developed pediatric D-lactic acidosis [44]. Another narrative review that focused on identifying potential applications of postbiotic supplementation in early life reported no significant side effects in healthy children [45].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the review found that a few cases in non-healthy infants (e.g., short bowel syndrome) fed with acidified formulas developed pediatric D-lactic acidosis [44]. Another narrative review that focused on identifying potential applications of postbiotic supplementation in early life reported no significant side effects in healthy children [45].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the probiotics, many studies reported useful efficiencies for postbiotics on host physiological parameters, including certain chemical structure, safety dose factors and prolonged shelf life [139,140]. The probiotics synthesize the postbiotics as non-viable or metabolic byproducts within the fermentation process, whose combination with other nutritional components can show health-promoting effects [141,142]. These compounds include organic acids, short chain fatty acids, endo-polysaccharides, exo-polysaccharides, peptides, cellular superficial proteins, plasmalogens, teichoic acids, muropeptides derived by peptidoglycan, and various enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Stress conditions, including HS, induce alterations in the microbiota balance, which may result in the colonization of enteric pathogens [63], and intestinal inflammatory responses [64]. Stabilization of the gut microbiota composition by pro-, pre-, syn-, and postbiotics is considered as an effective strategy to improve gut health and to protect the intestines against stress conditions [65][66][67][68].…”
Section: Microbiota Modulationmentioning
confidence: 99%